TiO2 Nanosphere/MoSe2 Nanosheet-Based Heterojunction Gas Sensor for High-Sensitivity Sulfur Dioxide Detection - Lanjuan Zhou; Chang Niu; Tian Wang; Hao Zhang; Gongao Jiao; Dongzhi Zhang (Nanomaterials)
With the growing severity of air pollution, monitoring harmful gases that pose risks to both human health and the ecological environment has become a focal point of research. Titanium dioxide (TiO2) demonstrates significant potential for application in SO2 gas detection. However, the performance of pure TiO2 is limited. In this study, TiO2 nanospheres and MoSe2 nanosheets were synthesized using a hydrothermal method, and the gas-sensing properties of TiO2/MoSe2 nanostructures for SO2 detection were investigated. The TiO2/MoSe2 composites (with a TiO2-to-MoSe2 volume ratio of 2:1) were characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), and X-ray diffraction (XRD). The TiO2/MoSe2 sensor exhibited high sensitivity to SO2; the response to 100 ppm of SO2 reached as high as 59.3, with a significantly shorter response and recovery time (15 s/13 s), as well as excellent repeatability, selectivity, and long-term stability. The experimental results suggest that the enhanced SO2 adsorption capacity of the TiO2/MoSe2 composite can be attributed to the formation of an n-n heterojunction and the unique microstructural features of TiO2/MoSe2. Therefore, the TiO2/MoSe2 sensor represents a promising candidate for rapid SO2 detection, providing a theoretical foundation for the development and application of high-performance SO2 sensors.